Separatism in Africa: The secession of South Sudan and its (un-)likely consequences - Denis Michael Tull (Stiftung Wissenschaft und Politik (SWP), 2011)
Some members of the international community, particularly in Africa, have mixed feelings about South Sudan's independence. Though most view the separation from Sudan as politically legitimate, they fear that the successful secession may have a signalling effect on separatist movements elsewhere in Africa. How valid is the assumption that the "precedent" of South Sudan will encourage secessionist tendencies which may change the continent's territorial map over the long run? And how should one consider Somaliland's claim for international recognition against the background of South Sudan's independence?
Keywords: 320